Mechanism of subunit interaction at ketosynthase-dehydratase junctions in trans-AT polyketide synthases - Jenner, Matthew; Kosol, Simone; Griffiths, Daniel; Prasongpholchai, Panward; Manzi, Lucio; Barrow, Andrew S.; Moses, John E.; Oldham, Neil J.; Lewandowski, Jozef; Challis, Gregory (Nature Publishing Group, 2018)
Modular polyketide synthases (PKSs) produce numerous structurally complex natural products with diverse applications in medicine and agriculture. They typically consist of several multienzyme subunits that utilize structurally-defined docking domains (DDs) at their N- and C-termini to ensure correct assembly into functional multi-protein complexes. Here we report a fundamentally different mechanism for subunit assembly in trans-AT modular PKSs at the junction between ketosynthase (KS) and dehydratase (DH) domains. This involves direct interaction of a largely unstructured docking domain (DD) at the C-terminus of the KS with the surface of the downstream DH. Acyl transfer assays and mechanism-based cross-linking established that the DD is required for the KS to communicate with the acyl carrier protein appended to the DH. Two distinct regions for binding of the DD to the DH were identified using NMR spectroscopy, carbene foot-printing and mutagenesis, providing a foundation for future elucidation of the molecular basis for interaction specificity.